A Systematic Review of Patient Complexity and Clinical Protocols: Acute-on-Chronic Multi-Morbidity Management in the Emergency Department - Alanazi, Abdulmajeed Obaid; Alshammari, Saleh Ashway Nahar; Al-Hazmi, A Majed Farhan Awad; Alhazmi, Owaed Awad; Alhazmi, Amer Mudhhi Suayn; Hakami, Tahani; Safar, Hanen Ibrahim; Al Enazi, Yusif Husin; Altayyari, Ayman Mohammed; Alharbi, Bandar Saleem; Albalawe, Nabeel; Alanazi, Khaled Fayez Zaal (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">The 21st-century Emergency Department (ED) is faced with a rising number of patients with complex multi-morbidity (CMM) presenting with acute deteriorations, or "acute-on-chronic" illness. These patients have intricate interactions between chronic diseases, polypharmacy, cognitive impairment, and social vulnerability that frustrate traditional single-organ emergency care and lead to diagnostic uncertainty, iatrogenic harm, and poor outcomes. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The aim of this review was to summarize the literature on acute-on-chronic CMM in the ED and present the argument for the need to develop specialized, interdisciplinary protocols for physicians and nurses to improve care for this vulnerable population. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative synthesis of the literature was conducted. The review analyzed the nature of CMM patients, critiqued existing care models like Geriatric ED guidelines, and proposed new protocol elements. Two new conceptual tools were developed: a nursing assessment framework and a formal communication tool for transitions in care. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The comparison confirmed the presence of a mismatch between CMM patient needs and usual ED functioning. While models like GEDA provide a foundation, a more comprehensive, protocol-based solution is required. The review prompted the creation of two helpful tools: a protocol for a thorough nursing assessment (covering cognition, function, and social context) and a standard handoff tool for ensuring safe transitions to primary care. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A paradigm shift toward proactive, holistic, protocol-driven care is required for acute-on-chronic CMM patients. Specialized interprofessional protocols are fundamental to advancing patient safety and promoting sustainable emergency care. Future research must focus on the validation of complexity screening tools and the evaluation of the impact of these protocols on patient-centered outcomes.